Expression of Thyroid Hormone Receptors in Villous Trophoblasts and Decidual Tissue at Protein and mRNA Levels Is Downregulated in Spontaneous and Recurrent Miscarriages. (July 2015) - Ziegelmüller, Brigitte; Vattai, Aurelia; Kost, Bernd; Kuhn, Christina; Hofmann, Simone; Bayer, Birgit; Toth, Bettina; Jeschke, Udo; Ditsch, Nina
Thyroid hormones are essential for the maintenance of pregnancy, and a deficiency in maternal thyroid hormones has been associated with early pregnancy losses. The expression of THRα1, THRβ1 and THRα2 increases with gestational age. The aim of this study was the investigation of the protein and mRNA-levels of THR isoforms THRα1, THRα2, THRβ1 and THRβ2 in normal, spontaneous and recurrent miscarriages. The identification of THR-expressing cells in the decidua was done with double immunofluorescence. The nuclear expression of THRα1, THRα2, THRβ1 and THRβ2 is downregulated at protein level in spontaneous and recurrent miscarriages in villous trophoblast tissue. In decidual tissue, we found a significant downregulation only for THRα1 in spontaneous miscarriages. For recurrent miscarriages, THRα1 and THRβ1 were both significantly downregulated in decidual tissue. By applying HLA-G as a trophoblast marker, we found a significant co-expression only for THRβ2. The results of our study show that thyroid hormone receptors THRα1, THRα2, THRβ1 and THRβ2 are downregulated in spontaneous and recurrent miscarriages. The majority of cells expressing the thyroid hormone receptors in the decidua are decidual stromal cells.